logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XI  >>  Math  >>  Binomial Theorem
0 votes

In the expansion of $(x+a)^n$ if the sum of odd terms is denoted by O and the sum of even term by E.Then prove that (i) $O^2-E^2=(x^2-a^2)^n$

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • $(x+a)^n=nC_0x^na^0+nC_1x^{n-1}a^1+nC_2x^{n-2}a^2+nC_3x^{n-3}a^3+.......+nC_n x^0a^n$
$(x+a)^n=nC_0x^na^0+nC_2x^{n-2}a^2+......)+nC_1 x^{n-1}a^1+nC_3x^{n-3}a^3+.....)$
$\therefore (x+a)^n=O+E$------(1)
Also $(x-a)^n =nC_0x^n a^0-nC_1 x^{n-1}a^1+nC_2x^{n-2}a^2-nC_3x^{n-3}a^3+......+(-1)^n nC_nx^0a^n$
$\therefore (x-a)^n=(nC_0x^n a^0+x_2 x^{n-2}a^2+.....)-(nC_1x^{n-1}a^1+nC_3 x^{n-3}a^3)$
$(x-a)^n$=O-E-----(2)
Now $O^2-E^2=(O+E)(O-E)$
$\Rightarrow (x+a)^n (x-a)^n$
$\Rightarrow (x^2-a^2)^n$
Hence proved.
answered Jun 24, 2014 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...